Given the expression:
![y=(1)/(3)x+1](https://img.qammunity.org/2023/formulas/mathematics/high-school/ql5jthrrm6xz1j9w5g45k8lg3q6v5r9jew.png)
To find the order pairs that are the solution of this equation, substitute x and find y. Then verify if the y found is the same as the y in the ordered pair.
a) (-6, -1).
Substituting x by -6:
![\begin{gathered} y=(1)/(3)\cdot(-6)+1 \\ y=-(6)/(3)+1 \\ y=-2+1 \\ y=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8u523upasjckedmlc40nbf6fl0i8uyz2vr.png)
The solution is (-6, -1) and the ordered pair is (-6, -1). Thus (-6, -1) is a solution.
b) (9, 4).
![\begin{gathered} y=(1)/(3)\cdot9+1 \\ y=(9)/(3)+1 \\ y=3+1 \\ y=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o4qoa1f3yznn6xt8i26zeibue96zxrgv2q.png)
The solution is (9, 4) and the ordered pair is (9, 4). Thus (9, 4) is a solution.
c) (-3, 0).
![\begin{gathered} y=(1)/(3)\cdot(-3)+1 \\ y=-(3)/(3)+1 \\ y=-1+1 \\ y=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wiuvh82uoovy5v23uyil7gojkcr8arct88.png)
The solution is (-3, 0) and the ordered pair is (-3, 0). Thus (-3, 0) is a solution.
In summary,
The order pairs (-6, -1), (9, 4) and (-3, 0) are solutions of the equation.